THE RUSSIAN ACADEMY OF SCIENCES: PAST AND FUTURE - I. P. Smirnov (Russian State Vocational Pedagogical University, 2016)
Abstract. The aim of the publication is the discussion of the most burning issues of reforming of the sphere of science and education and, first of all, consequences of the law «About the Russian Academy of Sciences, Reorganization of the State Academies of Sciences and Modification of Separate Legal Acts of the Russian Federation» (No. 253-FZ) adopted September 27, 2013.Results and scientific novelty. Firstly, the specified law was decently declared to be a narrow direction of «reorganization of the state academies of Sciences» and «separate changes»; the law has deeply affected all levels of the Russian science, mostly in a negative way. The attention is drawn to discrepancy of estimates of the undertaken reform, a vagueness of its aims and pseudo-reformatory installations of the separate entered legal acts, and also the fact that the expected results of transformations aren't even hypothetically formulated. All listed factors as a whole and deprivation of an academic community of activities autonomy pose a threat for full, real functioning and development of the scientific sphere that directly affects also a condition of all educational system in general. The origin suppositions of the state academies of sciences in Russia, history of their development and reforming, an origin of numerous public academies in education in the 90th years of the last century are considered on the basis of the retrospective, synchronous and diachronic analysis. Strategic miscalculations resulted the «nationalization» of science, replacement of the scientific self-government which isn't controlled by the state with a reliable departmental collarare disclosed on the example of the Russian Academy of Education. Practical significance. Based on the current situation, the author models functions of the Academy of Education; the functions are real and acceptable in its new status. Those functions come down to providing a qualified expert evaluation of drafts of regulations, state programs, pedagogical technologies and innovations, and also to implementation of publishing and printing activities - to publication and wide circulation of results of scientific researches.